HIV Cell Fusion Assay: Phenotypic Screening Tool for the Identification of HIV Entry Inhibitors via CXCR4. (January 2014) - Smith, Elizabeth B.; Ogert, Robert A.; Pechter, David; Villafania, Artjohn; Abbondanzo, Susan J.; Lin, Karen; Rivera-Gines, Aida; Rebsch-Mastykarz, Cheryl; Monsma, Frederick J.
The health and disease-related biology of the CXCR4 chemokine receptor presents the challenge of finding a small molecule that can bind CXCR4 and block T-cell tropic human immunodeficiency virus type 1 (HIV-1) cell entry, while preserving the ability of CXCR4 to respond to its native ligand, CXCL12. HIV entry into the host cell involves the interaction of the viral envelope glycoprotein gp120 binding to CD4, followed by a rearrangement in gp120, and subsequent interaction with the chemokine receptor CXCR4 or CCR5. These initial events can be re-created in a cell fusion assay that represents a surrogate system, mimicking the early stages of viral entry via these host cell receptors. In the current study, a T-tropic HIV cell fusion assay was established using U2OS cells expressing the envelope glycoprotein gp160 from the T-tropic HIV NL4-3 and HeLa cells expressing CD4 and CXCR4. Detection of the cell fusion event was based on a Gal4/VP16-activated β-lactamase signal and was measured by automated microscopy or laser scanning plate cytometry. Changes in morphology associated with cell fusion were combined with β-lactamase activity to generate results with robust assay statistics in both 384-well and 1536-well plates. Compounds were subsequently characterized by CXCR4 signaling assays to eliminate functional antagonists and allow the identification of a function-sparing HIV entry inhibitor.